Tránsito y Llegada de Refugiados Judíos y Sobrevivientes del Holocausto a México, 1939-1960 - Siman, Yael (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
During World War II, Mexico kept a selective and restrictive migratory politics towards the Jewish exile. Even though that politics was not singular in the region, it surprises that Mexico received only a group of 2,000 refugees. Despite this, Mexico became a permanent shelter for many refugees. The analysis focuses on the story of a survivor of the Holocaust -Bronislaw Zajbert- who was forced to move from his house in Lodz to be sent with his family to the ghetto of the city and emigrated first to Venezuela and later to Mexico. His experience swinging between the moving and the fixing contrasts the intensive mobility of those who managed to move in Europe to run away from Nazism. Their journey to Latin America emerges as a convergent experience while Mexico offered them in both cases the chance of finishing their displacement. It is an exploratory study that investigates how the individual experience of the transit impacted the construction of an affective and material home in Mexico.